Analytische Betrachtung der Bruchmechanismen in AlSiCu‐Gusslegierungen: Consideration of fracture mechanisms in AlSiCu casting alloys. Issue 7 (20th July 2018) - Papenberg, N.; Bozorgi, S.; Pippan, R.
Translation abstract: In this work the fracture toughness and responsible microstructural characteristics of AlSiCu casting alloys were investigated. A conventional A226 alloy and an alloy which is adapted for high temperature use were analyzed. A strong relationship between the cooling speed and the mechanical properties was found as well as the phases responsible for failure were identified.